2008
DOI: 10.2528/pierm08100601
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Shadow Region Effect on Radar Cross Section of Targets Using Physical Optics Method

Abstract: Abstract-Our method that uses current generator operator assumes the current on the entire surface of conducting scatterers. While, Physical Optics (PO) method assumes that the surface current generates only on the illumination region. The effect of the shadow region on the scattering waves is, therefore, proved by comparing our exact method with PO method. In this regard, radar cross-section (RCS) is calculated for smooth concave-convex contour. We work on numerical calculation of the RCS and analyze its char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Unfortunately, in the current literature there are few analytical models for the determination of RCS of composite targets (Barrick, ; El‐Ocla & Tateiba, ; Tateiba et al, ), even under the geometrical optics (GO) and the physical optics (PO) approximations. Several attempts have been made to find general and compact expressions for the bistatic scattering matrix starting from the more general framework of KA, but analytical formulas for the scattering coefficients are obtained only under the KA‐GO approximation (Elfouhaily & Guérin, ; Jin & Lax, ; Stogryn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in the current literature there are few analytical models for the determination of RCS of composite targets (Barrick, ; El‐Ocla & Tateiba, ; Tateiba et al, ), even under the geometrical optics (GO) and the physical optics (PO) approximations. Several attempts have been made to find general and compact expressions for the bistatic scattering matrix starting from the more general framework of KA, but analytical formulas for the scattering coefficients are obtained only under the KA‐GO approximation (Elfouhaily & Guérin, ; Jin & Lax, ; Stogryn, ).…”
Section: Introductionmentioning
confidence: 99%
“…The current generator is expressed in terms of wave-functions which satisfy Helmholtz equation and the radiation condition, and is well defined in [3,4]. For the second scattering problem, the excitation is chosen to be uniform plane and beam waves.…”
Section: Formulationmentioning
confidence: 99%
“…Recently we have presented numerical results for the backscattering enhancement in RCS of conducting cylinder with a concave-convex cross-section [3,4]. It has been found that the target configuration together with the SCL of the incident wave around the target play a leading role in determination of the RCS of partially convex targets.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier study, we aimed to apply our method on partially convex targets in random media with limited sizes and presented numerical results for exact RCS estimate and backscattering enhancement with putting into account the polarization of incident waves [4]- [6]. Later, we extended our study and considered large size targets in different random media [7].…”
Section: Introductionmentioning
confidence: 98%